Analisis Faktor yang Mempengaruhi Terjadinya Insiden Keselamatan Pasien - Fardiansyah, Arief; Romli, Ridoi Aka; Anggreni, Dhonna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The objectives of this research were analyzed patient safety culture, organizational communication climate, and task complexity towards patient safety incident in Hospital X. This research Method uses a analytic observational research with cross sectionalstudy design. Result of this research showed that patient safety culture and task complexity has significant influence towards patient safety incident, meanwhile organizational communication climate do not has significant influence towards patient safety incident. In conclusion, patient safety incidents that often occur in work units at Hospital X are near-injury incidents. Keywords: Organizational communication climate, patient safety incident, patient safety culture, task complexity